The Young Forever Cookbook - Hyman, Mark, 1959- (New York : Little, Brown Spark, 2023)
"Dr. Mark Hyman's ... book Young Forever revealed how to reverse the biological hallmarks of aging through easy and accessible dietary, lifestyle, and longevity strategies. In this companion cookbook, Dr. Hyman shares more than 100 satisfying recipes to help you eat your way to a longer life. Rooted in the latest science, the recipes [here] feature good fats, quality proteins, nutrient-dense vegetables, leafy greens, and a variety of other ingredients proven to support longevity. You'll find a range of meals and snacks designed to fight inflammation, boost your immune system, and promote healthy aging"--
Keywords: Cooking (Natural foods); High-protein diet -- Recipes; Low-carbohydrate diet -- Recipes; Vegetarian cooking; Longevity; Aging -- Prevention; Cookbooks